H.264/AVC decoder interprediction cache architectures - Densing, Chris Vincent J. (2013)
The use of cache memories in H.264/AVC interprediction mitigates the decoding bottleneck caused by off-chip memory accesses. This thesis explores two cache architectures suited for H.264/AVC interprediction memory access: the Split-Index cache, and the Last-Frame cache (LFC). Split-index architectures use a mapping of cache blocks which better exploits locality of reference in interprediction than a conventional cache. In this study, design-space exploration considering variables such as consideration, size, and associativity was performed. Their effects to cache performance were observed. Mapping windows that have aspect ratios of 1 were determined to be optimal. A 512-byte direct-mapped cache can have a 200% improvement in hit rate by using an optimal split-index architecture. Increased associativity also provides improvement in performance by allowing more flexible mapping of pixels blocks to the cache. LFC performance is highly dependent in the motion of objects within a video. An alternative write-back algorithm was introduced to increase performance in video with high top-to-bottom motion. It was applied in an adaptive LFC that switches between default and alternative write-back algorithms to maximize LFC performance. In targeted cases where high top-to-bottom motion occurs, the adaptive LFC in a QCIF decoder increases the hit rate by 2.5% to 4.5%. In general test cases, the adaptive LFC performs at par with the normal LFC. The use of the adaptive LFC incurs a hardware overhead in the form of additional logic characterizing motion and for modifying the write-back buffer.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Video compression -- Standards; Image stabilization; Split-index cache; Last-Frame cache